Poverty and Inequality in Thailand during the COVID-19 Pandemic 2020–2021 - Rakmumas, Wilasinee (Jurnal Informatika Ekonomi Bisnis, 2025)
Thailand is one of the countries that has faced chronic problems of poverty and inequality for a long time. But under the COVID-19 situation, even though Thailand is recognised as having one of the world's best systems for managing problems under the COVID-19 situation, it is still affected by COVID-19. This causes poverty and inequality in Thailand to become even more severe. According to the results of the survey, households with incomes below the standard have increased dramatically. Because there are expenses in terms of health, some households will need to spend more on health and must save some money for the next day. But under the COVID-19 situation, solving the problems of poverty and increasing inequality, the Thai government, under the leadership of Prime Minister Prayut Chan-o-cha, has borrowed money to alleviate poverty and inequality in Thai society and improve the situation. But because there are many waves of COVID-19, it makes dealing with it difficult. As a result, poverty in society at that time had a slow recovery, and due to other social factors, the poor group lacked opportunities and basic social rights.